FORMATION OF INFORMATIONAL CULTURE IN THE PROCESS OF FUTURE PHILOLOGISTS’ PROFESSIONAL TRAINING - Danylyuk, Serhiy (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
Specific features of formation of informational culture in the process of future philologists’ professional training are studied in the paper. Attempts to define the notion of informational culture are also made. Three levels of involving people to the world of computer science and computer engineering are singled out in the article. Besides, the set of abilities that future philologists who have informational culture should demonstrate is given.